2014
DOI: 10.1371/journal.pone.0106370
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Onset of Anxiety Syndromes at 12 Months in Primary Care Attendees. The PredictA-Spain Study

Abstract: BackgroundThere are no risk algorithms for the onset of anxiety syndromes at 12 months in primary care. We aimed to develop and validate internally a risk algorithm to predict the onset of anxiety syndromes at 12 months.MethodsA prospective cohort study with evaluations at baseline, 6 and 12 months. We measured 39 known risk factors and used multilevel logistic regression and inverse probability weighting to build the risk algorithm. Our main outcome was generalized anxiety, panic and other non-specific anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…Additional risk factors not directly related to diagnosis or treatment of breast cancer, including sociodemographic characteristics, comorbidities, medical history, and functional limitations, have also been shown to increase the risk of distress in the general population. In fact, many of these risk factors have been incorporated into predictive algorithms to estimate risk of incident distress in general practice [ 58 61 ]. Each of the algorithms includes younger age, indicator(s) of lower SES, and indicator(s) of perceived functioning limitations as predictors.…”
Section: Discussionmentioning
confidence: 99%
“…Additional risk factors not directly related to diagnosis or treatment of breast cancer, including sociodemographic characteristics, comorbidities, medical history, and functional limitations, have also been shown to increase the risk of distress in the general population. In fact, many of these risk factors have been incorporated into predictive algorithms to estimate risk of incident distress in general practice [ 58 61 ]. Each of the algorithms includes younger age, indicator(s) of lower SES, and indicator(s) of perceived functioning limitations as predictors.…”
Section: Discussionmentioning
confidence: 99%
“…To the authors' knowledge, the predictAL-10/9 is the first risk algorithm to predict the onset of HAD over 12 months in primary care. The predictAL-9/10 also had higher discriminative validity than the predictAL 15 and other risk algorithms for the onset of major depression [35][36][37][38] and anxiety syndromes 39,40 in primary care as well as for risk indices for cardiovascular events. 41,42 The study has some limitations.…”
Section: Strengths and Limitationsmentioning
confidence: 92%
“…The variable province had a relevant contribution in predicting the onset of HAD, major depression, 36 and anxiety syndromes. 39 This was also the case for country in international risk algorithms to predict such disorders, 15,35,40 and suggests that geographical variability must be taken into account in the prediction models. It is suggested that an average of the coefficients of the five Spanish provinces is used when the predictAL-10/9 is applied to obtain the probability of the risk of HAD outside Spain.…”
Section: Strengths and Limitationsmentioning
confidence: 95%
“…8,9 To our knowledge, there are no interventions to prevent the onset of anxiety disorders in the adult population irrespective of individual risk levels (universal prevention) administered by GPs. 7,10 Anxiety and depression frequently occur together, 11 they share most of their risk factors, [12][13][14] and both respond to the same treatments 15 and preventive interventions. [16][17] Our research group developed a personalized and novel bio-psycho-social intervention, the predictD-intervention, based on the level of risk and risk profile of depression and implemented by GPs to prevent the onset of major depression.…”
Section: Introductionmentioning
confidence: 99%